Management of periodontal disease in patients with diabetes- good clinical practice guidelines: A joint statement by Indian Society of Periodontology and Research Society for the Study of Diabetes in India - Ashish Jain; Manoj Chawla; Ashish Kumar; Rajeev Chawla; Vishakha Grover; Sujoy Ghosh; Nymphea Pandit; Purvi Chawla (Wolters Kluwer Medknow Publications, 2020)
There is a huge body of literature suggesting an association and a bidirectional relationship between periodontal disease and diabetes. Diabetes and periodontal diseases are both chronic diseases with a high prevalence. Dentists/periodontists, in their daily clinical practice, very often attend to diabetes patients with diverse oral health conditions and cater to their dental treatment needs. Safe and effective periodontal therapy in this population requires a broad understanding of diabetes, medical management of diabetes, and essential modifications to dental/periodontal therapy that may be required. This paper describes a joint statement put forth by the Indian Society of Periodontology and the Research Society for the Study of Diabetes in India aiming to provide expert consensus and evidence-based guidelines for optimal clinical management of periodontal conditions in diabetes patients or patients at risk for diabetes. Although this paper is not envisioned to be a comprehensive review of this topic, it intends to provide the guidelines for dental professionals and periodontists.